Effect of tire pyrolysis oil, crude palm biodiesel and engine speed on engine performance - Jaat, Norrizam; Khalid, Amir; Sulaiman, Syabillah; Azizul, Muhamad Asri; Mohamed, Norirda; Salleh, Hamidon; Razali, Azahari; Mohamed Sunar, Norshuhaila; Abdul Jalal, Rifqi Irzuan (2024)
Diesel combustion engine which the air is compressed to a sufficiently high temperature used to ignite diesel fuel injected into cylinder, where ignition, burning combustion and expansion actuate a piston. Due to limited resources of fossil fuel, the new alternative fuel is rise and now biodiesel became attention in the automotive industries sector. The purpose of this research is to investigate the effect of tire pyrolysis oil, crude palm biodiesel and engine speed on engine performance. Two cylinders four strokes cycle, air cooled, compression ignition was used to conduct this experiment. Then, the data was collected by PC based software from the experiment to show its performance. This engine experiment done by using blended biodiesel from blended tire pyrolysis oi l (TPO) that is TPO20 and TPO25 and also standard diesel (STD). Next the experiment also had done run using blended biodiesel from blended crude palm oil (CPO) which was CPO10 and CPO15 and also standard diesel (STD). The engine were done run at different speed for 1200rpm, 1400rpm, 1600rpm, 1800rpm and 2000rpm. The results of the engine performance were compared in different calculations which were brake power, torque, brake specific fuel consumption, brake thermal efficiency and the exhaust gas temperature. The development of the biodiesel technology will give an alternative fuel for the diesel engine user in order for them to do their daily routine